EVALUASI PENGGUNAAN OBAT ANTITUBERKULOSIS (OAT) PADA PASIEN TB PARU DI PUSKESMAS PUNGGUR KABUPATEN LAMPUNG TENGAH PERIODE OKTOBER 2022 - OKTOBER 2023 - Akhmad Rokiban; Kiky Maykasari (Jurnal Farmasi IKIFA, 2024)
Tuberculosis is a infectious chronic disease caused by Mycobacterium tuberculosis. Based on WHO data the incidence of tuberculosis in Indonesia reached 842 thousand cases with a mortality rate of 107 thousand cases. To eradicate tuberculosis, one of which can be realized by the use of antituberculosis drugs by National Guidelines Standards. The purpose of this study was to evaluate the suitability of the use of OAT for pulmonary tuberculosis patients in Punggur Public Health Center, Central Lampung Regency from October 2022 - October 2023 based on the "National Guidelines for TB Prevention" by the Indonesian Ministry of Health in 2016.This type of research is a non-experimental study with a descriptive research design and retrospective approach of the medical record of pulmonary tuberculosis patients in Punggur Public Health Center, Central Lampung Regency, October 2022 - October 2023. Data were processed descriptively using Microsoft Excel program into a form of percentage table data. The results showed that cases of pulmonary TB were more common in male patients at 61.4%. Patients who used type 1 OAT were 93.2% while patients who used category 2 OAT were 6.8%. The pattern of using OAT in pulmonary TB patients is KDT OAT as much as 100%. Based on conformity to the "National Guidelines for TB Prevention" by the Indonesian Ministry of Health, 2016, the results of the indication of conformity of 97.7%, the suitability of the combination of 100% and e suitability of the dose of 88.6% with the result of treatment 95.5% of patients cured and 4.5% of patients were declared not cured.